An attempt to assess the usefulness of Google Scholar as a data source for entomological review papers on the example of the description of the biology of Anomala dubia (Scopoli, 1763) (Coleoptera: Scarabaeidae) - Bochniarz, Alina (Polish Journal of Agronomy, 2024)
Review papers, especially those with features of meta-analysis, are a valuable part of the scientific literature, both from the point of view of specialists and researchers seeking information in fields new to them. The basis of this type of publication is the proper selection of study sources. The aim of this study was to assess the usefulness of the Google Scholar search engine in the selection of material for review papers in entomology. The analysis was based on a sample assignment involving the characterisation of the beetle species Anomala dubia. Problems arising in using the retrieved resource were identified and assigned to selected categories. The search results included almost all relevant records from the SCOPUS and Web of Science databases, plus a number of potentially valuable publications from other sources. The collected material was not sufficient to characterise the studied species in detail, but this could also be due to the lack of digitalised data in the available literature resources.